Locomotor Activity Monitoring in Mice to Study the Phase Shift of Circadian Rhythms Using ClockLab (Actimetrics) - Andrea Brenna; Jürgen Ripperger; Urs Albrecht (Bio-Protocol)
The circadian clock regulates biochemical and physiological processes to anticipate changes in light, temperature, and food availability over 24 h. Natural or artificial changes in white/blue lighting exposure (e.g., seasonal changes, jet lag, or shift work) can advance or delay the clock phase to synchronize physiology with the new environmental conditions. These changes can be monitored through behavioral experiments in circadian research based on the analysis of locomotor activity by measuring wheel-running revolutions. The protocol includes measuring the internal period length in constant darkness and administering nocturnal light pulses to mice kept either in light/dark conditions (LD 12:12, Aschoff-type II protocol) or continuous darkness (DD, Aschoff-type I). Here, we describe a step-by-step guide for researchers to analyze the mouse circadian clock using wheel-running experiments and ClockLab (Actimetrics) to quantify data.